Methods to determine saddle height in cycling and implications of changes in saddle height in performance and injury risk: A systematic review - Bini, R.; Priego-Quesada, J. (Journal of Sports Sciences, 2022)
The objective of this systematic review was to assess the methods to determine bicycle saddle height and the effects of saddle height on cycling performance and injury risk outcomes. The key motivator of this review was to update and expand the finding reported by a previous narrative review published in 2011. The literature search included all documents from the following databases: Medline, Scopus, CINAHL, OVID and Google Scholar. Studies were screened against the Appraisal tool for Cross-sectional Studies to assess methodological quality and risk of bias. After screening the initial 29,398 articles identified, full-text screening was performed on 66 studies with 41 of these included in the systematic review. Strong evidence suggests that saddle height should be configured using dynamic measurements of the knee angle, and limb kinematics is influenced by changes in saddle height. However, moderate evidence suggests that changes in saddle height less than 4% of the leg length results in trivial to small changes in lower limb loads, and no effect on oxygen uptake and efficiency. It is also possible to state that there is limited evidence on the effects from changes in saddle height on supramaximal cycling performance or injury risk.